Teachers’ beliefs about the physical education and sports profession and their impact on quality of work life - Alper Sayin, Ahmet; Karayazi, Tulay; Yavuz Eroglu, Sultan; Uzer, Yunus (SPORT TK-EuroAmerican Journal of Sport Sciences, 2025)
This study examined the impact of physical education teachers’ beliefs about their profession on their quality of work life. The research sample consisted of 90 physical education and sports teachers (17 female, 73 male) employed in schools affiliated with the Ministry of National Education in Siirt Province, Turkey. The researchers utilized personal information forms, the “Quality of Work Life Scale” and the questionnaire “Physical Education Teachers’ Beliefs about the Physical Education Profession”. The findings revealed that there was a significant positive relationship between overall beliefs about the profession and quality of work life (r = 0.244, p = 0.021). Regression analysis revealed that the overall beliefs about the profession were significant predictors of quality of work life (β = 0.244, p = 0.021). Of the overall beliefs, the value of the physical education profession had a significant positive effect on quality of work life (β = 0.255, p = 0.015), while sense of calling had no significant effect (p > 0.05). Beliefs about the profession were found to be significant predictors of individual quality of work life (p < 0.01), while the relationship between overall beliefs about the profession and organizational quality of work life was weaker and not significant (p > 0.05). In conclusion, the relationship between teachers’ beliefs about the profession and their quality of work life represents a significant area of inquiry within the field of physical education.